Assessment of Tehran University of Medical Sciences Website Based on Webometrics Criteria at 2008 - F Azadeh; H Zeraati; SJ Ghazi mirsaeed; SB Miralai (Tehran University of Medical Sciences, 2009)
Background And Aim: Nowadays university websites are very important in information services. There fore university has designed website for categorizing and availability of mass of information . This study accomplish to purpose evaluated of Tehran university of medicine sciences website base on webometrics criteria on 2008 .Materials and Methods: This survey have been used link analysis methods by four criteria : visibility , size , rich file and google scholar . The situation of Tehran university of medicine sciences website has surveyed . Data gathering tools at webometrics survey are search engines . Data are gathering at google , yahoo, live search and exalead search engine . For data analysis used Excel software.Results: Findings showed that , visibility of Tehran university of medicine sciences website with 9562 inlinks are weak , nevertheless published research at google scholar with 12100 articles , have suitable ranked in region and world. also size of university website depended to indexing of search engine , web of university often indexing at google and yahoo , less than at live search and exalead .10813 pages published at Rich files format on google , website of university tend to publish rich files as format of .pdf and then .Doc and .ppt . Average load time for tums with 4.2 second is not desirable.Discussion and Conclusion: Number of papers and citations for tums domain at google scholar is very good at world and middle east. Number of pages recovered from Google, Yahoo in Persian language are optimum but pages from Live Search and Exalead in English language is not favorable . The total number of unique external links received to tums website from Iranian university website is good but from international and information institution is low .